2011
DOI: 10.1021/jp112263s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquid on J-Aggregation ofmeso-Tetrakis(4-sulfonatophenyl)porphyrin within Aqueous Mixtures of Poly(ethylene glycol)

Abstract: Aqueous mixtures of poly(ethylene glycol) (PEG) of different compositions offer widely varying physicochemical properties that may support porphyrin aggregation. Aggregation behavior of a common water-soluble porphyrin, meso-tetrakis(4-sulfonatophenyl)porphyrin (TPPS), is investigated within aqueous PEG mixtures constituted of PEGs of average molecular weights 200 (PEG200), 400 (PEG400), 600 (PEG600), and 1000 (PEG1000) using UV-vis molecular absorbance, steady-state fluorescence, and resonance light scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…Then, when the effects of both cosolvents, ethanol and PEG 400 were compared at the same proportion mixtures with water, it was clear that PEG 400 favored more the monomeric species of the compound, in agreement with the literature [19,33] therefore, this solvent is more relevant for different biological environments.…”
Section: M)supporting
confidence: 84%
See 1 more Smart Citation
“…Then, when the effects of both cosolvents, ethanol and PEG 400 were compared at the same proportion mixtures with water, it was clear that PEG 400 favored more the monomeric species of the compound, in agreement with the literature [19,33] therefore, this solvent is more relevant for different biological environments.…”
Section: M)supporting
confidence: 84%
“…NR and NRBr were studied in different solvents which increase the quantity of monomers in solutions such as DMF [20,32] and PEG 400 [19,33] both known to be good monomerizing solvents, to continue the studies of the monomer form of dyes and to attempt to corroborate the assignation of the different bands.…”
Section: As Evident Frommentioning
confidence: 99%
“…In regard to IL-controlled intramolecular processes, we reported on the ability of ILs to modulate conformational equilibrium (twisted versus extended conformation) of tetracycline by simply varying the nature of the anion in a series of 1-butyl-3-methylimidazolium ILs. 25 As examples of intermolecular interactions in ILs, the Jaggregation of porphyrins [26][27][28][29][30] and J-/H-aggregation of cyanine dyes 31,32 in ILs were reported. Importantly, in the case of a cyanine dye, it was shown that the formation of Haggregates in [C 4 -mim]BF 4 was triggered by the addition of small amounts of NaOH, while J-aggregates were formed in [C 4 -mim]PF 6 , [C 4 -mim]NTf 2 , [C 4 -mim]OTf, and a few other ILs, also upon addition of small quantities of NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade much work has been done on TPPS interactions with surfactants, [7][8][9][10][11] polyelectrolytes [12][13][14][15] and especially biomacromolecules. [16][17][18] The increasing research interest in porphyrin behavior within microorganized systems is due to their possible application as photosensitizers in photodynamic therapy (PDT), [19] since the microheterogeneous medium is known to favor supramolecular ionic associate and 341 Макрогетероциклы / Macroheterocycles 2013 6(4) 340-344 M. A. Gradova, A. V. Lobanov heteroaggregate formation, especially at low pH abundant in cancer cells.…”
Section: Introductionmentioning
confidence: 99%